Penilaian Otentik dan Implementasinya dalam Pembelajaran Matematika di SMAN 01 Lambitu - Azra Fauzi (P-2623-0291)
Assessment is one of the important things in education. Authentic assessment is a process to describe changes in students after learning. The purpose of this article is to describe the use of authentic assessment in SMAN 01 Lambitu based on the results of an analysis of document studies and interviews with one of the mathematics teachers in the school regarding the implementation of authentic assessment in mathematics learning. This research uses a qualitative approach with descriptive type. The subject of this research is a mathematics teacher at SMAN 01 Lambitu. Data collection techniques used are through document review and interviews. The results of this study indicate that the teacher gives an analytical assessment, which provides scoring based on the steps of student work in answering the questions given. The teacher also views authentic assessment as being able to represent students 'abilities and is effective in identifying students' weaknesses or problems in completing assignments. This makes it easier for teachers to guide students in the next learning process